Development of a shielding device for radiotherapy of breast cancer-bearing mice - Camila R. Silva; Saulo Toledo Pereira; Celia Marina Napolitano; Elizabeth Ribeiro Somessari; Martha Simões Ribeiro (Brazilian Journal of Radiation Sciences, 2020)
Breast cancer is the fifth most common cause of death worldwide. Currently, one of the standard treatments for breast cancer is radiation therapy (RT).  On the other hand, mouse models have been used in pre-clinical studies for breast cancer RT, requiring dedicated shielding to exposure the breast region. In this work, we considered the values of the lead attenuation coefficient and the tenth reducing layer for a 60Co irradiator and developed a lead shielding device for breast cancer-bearing mice to be exposed to localized breast RT. Five-kg of lead were exposed to temperature of 340ºC and inserted into an aluminum mold previously adjusted to the dimensions of the device. After solidification, the device was shaped into a cylinder with dimension of 14 x 15 x 7 cm (height x width x thickness, respectively). A round cut-out for breast exposure of 1 cm in diameter was made at 5 cm from the basis of the device. For shielding device validation, we performed calibrations to establish a dose of 10 Gy in the target. Fifteen CaSO4:Dy thermoluminescent dosimeters were distributed along a 50 mL conical tube to simulate the mouse position inside the shielding. The shielding device was placed at a fixed distance of 10 cm from the target for optimal exposure time. After irradiation, the dosimeters were read on a thermoluminescent reader. According to our results, we were able to develop a body-shielding device that assured the required dose for RT of breast cancer in mice.